Protease Activity Assay in Fly Intestines - Marie-Paule Nawrot-Esposito; Rihab Loudhaief; Armel Gallet (Bio-Protocol, 2017)
The intestine is a central organ required for the digestion of food, the absorption of nutrients and for fighting against aggressors ingested along with the food. Impairment of gut physiology following mucosal damages impacts its digestive capacities that consequently will affect growth, wellbeing or even survival of the individual. Hence, the assessment of intestinal functions encompasses, among others, the monitoring of its integrity, its cellular renewing, its immune defenses, the production of enteroendocrine hormones and its digestive capacities. Here, we describe in detail how to assess the activity of the proteases secreted in the intestinal lumen of adult Drosophila melanogaster flies. This method can also be used for larval intestines. The present protocol is adapted and improved from the Sigma-Aldrich’s protocol proposed in the ‘Protease Fluorescent Detection Kit’ (Product code PF0100).